Antiplasmodial Isoflavanes and Pterocarpans from Apoplanesia paniculata - Su, Qingxi; Krai, Priscilla; Goetz, Michael; Cassera, Maria B.; Kingston, David G. I. (Planta Medica, 2015)
Bioassay-guided fractionation of an EtOH extract of the roots of the plant Apoplanesia paniculata (Fabaceae) led to the isolation of the three known compounds amorphaquinone (1), pendulone (2), and melilotocarpan C (3), and the two new pterocarpans 4 and 5. Compounds 1 and 2 exhibited good antiplasmodial activity with IC50 values of 5.7 ± 1.5 and 7.0 ± 0.8 µM, respectively. Compound 3 exhibited weak antiplasmodial activity (41.8 ± 5.2 µM), while compounds 4 and 5 were inactive. Compound 6 was synthesized to confirm the structure of 5, and it showed enhanced antiplasmodial activity (15.8 ± 1.4 µM) compared to its analogues 3–5.
Keywords: antimalarial activity; isoflavanes; pterocarpans; Apoplansia paniculata (Fabaceae)